Sejarah Reformasi Pendidikan Islam di Universitas Al-Azhar dan Jejak Pengaruhnya di Masa Kontemporer - Adiska Nur Anggraeni; Aniqo Shofia Rahma; Meli Astutianingsih; Mukhammad Yusuf Abdul Fattah (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This study aims to map the historical transformation of Islamic educational reform at Al-Azhar University in Cairo and analyze its impact on contemporary Islamic educational practices. A qualitative approach using historical-analytical methods was employed through library research, analyzing secondary and tertiary data sources such as academic journals, books, and encyclopedias. The research findings reveal three complementary patterns of reform: modernization oriented toward the European educational system, which incorporated rational sciences and natural sciences into the curriculum; the purification of Islamic teachings through the revival of ijtihad, which opposed the culture of taqlid and encouraged critical and dialogical thinking; and the internalization of the values of nationalism and local cultural identity as the foundation for national character building. Figures such as Muhammad Ali Pasha, Jamaluddin Al-Afghani, Muhammad Abduh, and Rifa’ah al-Tahtawi played a crucial role in dismantling the dichotomy between religious and secular knowledge, and in laying the foundations for a rational and contextual pedagogy. The pinnacle of structural reform was achieved through Law No. 103 of 1961, which integrated Al-Azhar into the framework of a modern university. In the contemporary context, the legacy of this reform is manifested in curriculum integration, the strengthening of religious moderation (wasatiyyah), and the adoption of digital technology in learning. This study concludes that Al-Azhar’s reform model, which synthesizes classical scholarly traditions (turath) with modernity, can serve as a strategic framework for developing adaptive and holistic Islamic education in the 21st century.   Keywords: Al-Azhar University, Educational Reform, Islamic Education, Islamic Modernization, Muhammad Abduh